The Effect of The Pandemic on The Learning Outcomes of Vocational High School Students: In Terms of Perception, Learning Readiness, and Stress Level - Miftanisa, Fahna Sabilla; Suharno; Estriyanto, Yuyun; Pambudi, Nugroho Agung (Jurnal Pedagogi dan Pembelajaran, 2023)
During the pandemic, the government implemented an online mode of learning. However, there is an unpreparedness of the school in managing this mode of learning, therefore student competence does not develop. This study aims to analyses the effect of student perceptions, learning readiness, and stress levels on learning outcomes during the pandemic. The research approach used is quantitative with a survey and correlational design. Random sampling technique was used with a total sample of 149 of Vocational High School students. Furthermore, questionnaires and student scores were used for data collection. The data analysis technique is carried out using categorization based on Azwar's theory. The results showed that student' perceptions, readiness to learn, and stress levels had a significant effect on learning outcomes. The role of teacher needs to improve learning patterns; therefore learning is more interesting and establishes good communication with students. Parents must provide a conducive learning place. Meanwhile during the pandemic, teachers need to pay attention in giving assignments, therefore this does not make students overwhelmed and depressed. The implication is that teachers must design more innovative learning so that students are enthusiastic. Therefore, practical learning innovations are important to be developed further.